1980
DOI: 10.1111/j.1528-1157.1980.tb04313.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Study of the Pattern of Spontaneous Activity of Cerebellar Purkinje Cells and Phenytoin Serum Levels in the Rat

Abstract: The effects of phenytoin (PHT) on the spontaneous activity of cerebellar Purkinje cells and the drug serum levels have been examined following both intravenous and intraperitoneal administration in rats. Purkinje cell activity was assessed by on-line computer analysis of interspike interval distributions. PHT levels were assayed in blood samples taken at the end of the electrophysiological experiments and in successive samples obtained in parallel experiments over periods corresponding to when electrophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The sig- nificantly higher increase of cerebellar level is consistent with PHT brain binding and a drug sequestration in the CNS by limitedexit kinetics (Ramsay et al, 1979;. The increase in P-cell firing rate induced by PHT is in agreement with the findings by Halpern and Julien (1972), Julien (1974), Julien andLaxer (1974), andShimizu et al (1977), but it is contrary to the observations of Puro and Woodward (1973) and Latham and Paul (1980). Beyond the possible effects of different doses, treatment schedules, and animal species, one can observe that all the experiments, including our own, indicating a PHT-induced increase in P-cell firing rate were performed in awake paralyzed animals.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The sig- nificantly higher increase of cerebellar level is consistent with PHT brain binding and a drug sequestration in the CNS by limitedexit kinetics (Ramsay et al, 1979;. The increase in P-cell firing rate induced by PHT is in agreement with the findings by Halpern and Julien (1972), Julien (1974), Julien andLaxer (1974), andShimizu et al (1977), but it is contrary to the observations of Puro and Woodward (1973) and Latham and Paul (1980). Beyond the possible effects of different doses, treatment schedules, and animal species, one can observe that all the experiments, including our own, indicating a PHT-induced increase in P-cell firing rate were performed in awake paralyzed animals.…”
Section: Discussionsupporting
confidence: 77%
“…Beyond the possible effects of different doses, treatment schedules, and animal species, one can observe that all the experiments, including our own, indicating a PHT-induced increase in P-cell firing rate were performed in awake paralyzed animals. On the contrary, Puro and Woodward (1973) and Latham and Paul (1980) worked with alothane and urethane anesthesia, respectively. The effect of these two anesthetic agents on cerebellar activity has not yet been reported, but both drugs induce an impairment in mitochondria1 function (Cohen, 1973;Grist and Baum, 1974;Ginsberg et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The augmentation of Purkinje cell activity by antiepileptic drugs was first proposed as a mechanism of action by Julien and Halpern (1971), who found that anticonvulsant doses of phenytoin increased the firing rate of Purkinje cells in unanesthetized, curarized cats. Although some investigators have confirmed these results in cats (Shimizu et al, 1977;Fernandez-Guardiola et al, 1979), others have failed to demonstrate phenytoin-induced augmentation of Purkinje cell activity in cats (Latham and Paul, 1976) and rats (Pieri and Haefely, 1976;Puro and Woodward, 1973;Latham and Paul, 1980). These conflicting results may have arisen from differences in experimental animals, anesthetic protocols, microelectrode recording techniques, and/or phenytoin doses and routes of administration.…”
mentioning
confidence: 99%